2016
DOI: 10.1111/apm.12623
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of primary diffuse large B‐cell lymphoma of the central nervous system – strong EZH2 expression implying diagnostic and therapeutic implication

Abstract: Primary diffuse large B-cell lymphoma of the central nervous system (CNS DLBCL) is a rare entity which is difficult to diagnose and treat. The histone methyltransferase EZH2 was reported to be involved in the tumorigenesis of systemic DLBCL but has not been implicated in primary CNS DLBCL. The clinicopathological features of 33 cases of primary CNS DLBCL and expression of EZH2 and Y641 mutation were assessed. The tumor cells of the majority cases resembled centroblasts, and intriguingly, three cases of rare an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The former is positive for CD30 and/or ALK and negative for B-cell markers, whereas primary CNS A-DLBCL expresses B-cell markers with negativity for ALK. Negativity for cytokeratin is helpful in distinguishing this type of DLBCL from undifferentiated carcinoma [14].…”
Section: Discussionmentioning
confidence: 99%
“…The former is positive for CD30 and/or ALK and negative for B-cell markers, whereas primary CNS A-DLBCL expresses B-cell markers with negativity for ALK. Negativity for cytokeratin is helpful in distinguishing this type of DLBCL from undifferentiated carcinoma [14].…”
Section: Discussionmentioning
confidence: 99%
“…76,77 EZH2 is expressed, but without evidence of gene mutation. 75 PD-L1 is positive in approximately 30% of cases 78 CD10 is positive in less than 20% of cases, CD30 is positive rarely, and CD138, T-cell markers and EBER1 are negative. 1,76 Cytogenetics and molecular Chromosomal alterations involving 9p21.3, 6p, 6q, chromosome 12, 18q21.33-23, and 10q23.2 have been shown.…”
Section: Immunophenotypementioning
confidence: 98%
“…Surrounding reactive gliosis or lymphocytic infiltrates may be noted. 75 Endothelial proliferation or pseudo-palisading necrosis, as seen in glioblastoma, is not a feature.…”
Section: Histomorphologymentioning
confidence: 99%
“…[22] In contrast, Guo et al found that MYC expression alone and MYC/BCL-2 co-expression was significantly associated with poor outcome in patients with PCNS-DLBCL. [34] Kim et al summarized that patients with MYC/BCL-2 co-expression exhibited worse progression-free survival (PFS) in the MTX-treated group, and the same conclusion was got in Shi study. [25,23] Similarly, our research found that patients with c-MYC/BCL2 co-expression trended towards a poor prognosis.…”
Section: Discussionmentioning
confidence: 63%